Simulation of Seizures for the Pediatrics Resident - Suzanne Friedman; Meghan Tozzi; Victoria Shakhin; Keila Veiga; Scott Moerdler; Abigail Carey; Sheemon Zackai (Association of American Medical Colleges, 2014)
Abstract This resource features a guide for teaching about seizures, as well as a detailed manual for simulation of seizure activities geared towards pediatric interns and residents. The detailed instructor's manual provides the framework for the initial simulation case, which is followed by an educational slide presentation for which the instructor's manual provides detailed talking points. This is followed by a second simulation case, also detailed in the instructor's manual. Pediatric emergencies are not commonplace, but when the situation arises residents must be prepared. This simulation activity reviews general knowledge of seizures, a common pediatric condition, as well as reviews team and leadership roles and provides the residents with the opportunity to practice their skills in a real-time case.